Qualidade de vida de pacientes hipertensos de um centro de referência no tratamento de hipertensão arterial - CARVALHO, Maria Virgínia de (2012)
INTRODUCTION: Systemic Arterial Hypertension (SAH) is one of the main cardiovascular risk factors, with high prevalence in almost every country. Studies have shown the negative effect of SAH on health-related quality of life (HRQL). OBJECTIVES: To evaluate the quality of life of hypertensive patients compared to the general population. METHODS: The study included patients of both sexes over 18 years of age. The EG, consisting of medicated patients enrolled in a multi-disciplinary SAH treatment service, responded to two HRQL evaluation instruments: one, the SF-36, was generic, and the other, MINICHAI-Brasil, was specificSAH treatment service, responded to two HRQL evaluation instruments: one, the SF-36, was generic, and the other, MINICHAI-Brasil, was specific. In the CG, consisting of normotensive individuals from the community, only the SF-36 was administered. For statistical analysis, the chi-square, Komogorov-Smirnov, Mann Whitney and Kruskal-Wallis tests and multivariate analysis were used. SPSS was used to analyze the data and p values <0.05 were considered significant. RESULTS: The groups were homogeneous with regard to age, sex, ethnic group, education level and marital status. Normotensive individuals had higher HRQL scores than hypertensives on the SF-36 in all domains. There was no significant difference between the study and control groups in regard to the emotional aspect EA (p=0.36). On the MICHAL-Brasil, SAH significantly affected HRQL in the mental state (MS) domain and least affected younger individuals with more schooling and higher income living with a partner. CONCLUSION: Although SAH is considered to be a silent and asymptomatic disease, it affects HRQL and is apparently associated with psycho-social factors and conditions.